ClimBeR analyses position climate-security risks at the top of national, regional, and pan-African policy agendas for a more resilient and peaceful future. - Pacillo, Grazia (2024)
CGIAR’s Climate Resilience Initiative (ClimBeR) analyses — produced under the Climate Security Observatory (CSO) — informed the strategic direction of the Intergovernmental Authority on Development Center of Excellence for Climate Adaptation and Environmental Protection (IGAD-CAEP) and the African Union towards adopting stronger climate-security sensitive policy measures. Together with the Cairo International Center for Conflict Resolution, Peacekeeping and Peacebuilding, and the Africa Group of Negotiators Expert Support (AGNES), the Alliance, through ClimBeR, increased African negotiators’ and policymakers’ capacities and knowledge on climate security issues in Africa.